IMPLEMENTATION OF THE MUDHARABAH CONTRACT AT UJUNG GADING MARKET, WEST PASMAN REGENCY - Muhammad Jahar Bulek; Mursal Mursal; Julhadi Julhadi (Yayasan Adra Karima Hubbi, 2025)
Mudharabah is an Islamic economic contract based on cooperation between capital owners (shahibul mal) and business managers (mudharib). In practice, its application often faces challenges such as information imbalance, low Islamic financial literacy, and potential deviations from sharia principles. In Ujung Gading Market, West Pasaman Regency, mudharabah contracts have the potential to empower small and medium-sized traders. This study examines the implementation of mudharabah contracts in the market, their effectiveness in improving traders’ welfare, and the obstacles encountered. A qualitative approach was used with data collection through in-depth interviews, field observations, and documentation studies. Informants included traders, capital owners, and stakeholders managing mudharabah contracts. The findings show that mudharabah contracts contribute to increased income and strengthened business networks. However, obstacles such as low understanding of sharia principles, lack of local regulatory frameworks, and limited capital access hinder their full potential. This study is limited by its narrow area coverage and lack of quantitative data to support qualitative findings. Further research with a broader scope and quantitative methods is recommended to enhance the analysis of mudharabah contract effectiveness in local and global contexts.